The application of competition policy vis-à-vis intellectual property rights: The evolution of thought underlying policy change - Robert D. Anderson; William E. Kovacic (World Trade Organization (WTO), 2017)
This paper examines the evolution of national competition (antitrust) policies and enforcement approaches vis-à-vis intellectual property rights (IPRs) and associated anti-competitive practices in major jurisdictions over the past several decades. It focuses especially on the underlying process of economic learning that has, the authors suggest, driven relevant policy changes. Part 2 of the paper outlines the breakthroughs in understanding that have underpinned the evolution of competition policy approaches toward intellectual property licensing arrangements in the US, Canada and the EU. Part 3 elaborates the foundational insights that have motivated competition policy interventions with respect to 'newer' issues such as anti-competitive patent settlements and hold-ups in relation to standard setting processes, in addition to the modern focus on mergers that potentially lessen incentives for innovation and on abuse of dominance/single firm exclusionary practices in IP-intensive network industries. Part 4 outlines some of the core policy concerns and insights driving the increased emphasis that leading competition authorities now devote to policy advocacy and research in relation to the scope and definition of IP rights. Overall, the analysis suggests, firstly, that competition policy applications in the intellectual property sphere are matters of fundamental importance for economic advancement and prosperity, having a direct bearing on innovation, growth and the diffusion of new technologies. Indeed, the roles of IP and competition policy are now sufficiently intertwined and interdependent that neither can be well understood or applied in an optimal fashion in the absence of the other. Secondly, the thought evolution described herein implies that successful policy applications require careful study of market structure and behaviour, not in the abstract but with reference to the particular markets affected. Thirdly, it augurs favourably for the prospects of continuing gradual and incremental convergence in national approaches in this area, even spanning developed and developing countries, on the basis of continual learning and informed self-interest.
Keywords: K21; L4; L41; L43; O3; O34; 330; intellectual property; patents; international trade and competition policy; antitrust; innovation; mergers; anti-competitive settlements; standards; network industries; competition advocacy